Synthesis and hypoglycemic activity of quinoxaline derivatives - Jia, Weidong; Wang, Jingjing; Wei, Chengxi; Bian, Ming; Bao, Shuyin; Yu, Lijun (Frontiers in Chemistry, 2023)
In this study, a new series of quinoxalinone derivatives (5a–5p, 6a–6n) was designed and its hypoglycemic activity was evaluated. The results showed that compounds 5i and 6b exhibited stronger hypoglycemic effects than the lead compounds and were comparable to the positive control Pioglitazone. 5i and 6b may exert hypoglycemic effects by alleviating cellular OS and modulating the interactions among GLUT4, SGLT2, and GLUT1 proteins. The alleviating cellular OS of compound 6b was better than that of 5i, and 6b was found to bind better than 5i for most of the screening targets. In summary, compound 6b is a potential lead compound with hypoglycaemic activity.3